Edukasi Gangguan Siklus Menstruasi pada Pasangan Usia Subur (PUS) di Desa Bangun Rejo Kecamatan Tanjung Morawa Tahun 2024 - Dewi Sartika Hutabarat; Edi Subroto; Retno wahyuni; Cristoboy Vasius Bakara; Lisa Sibarani; Cindy Shintia (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background Sexual health is defined as a state of complete physical, mental and social well-being, not merely the absence of disease or disability in all matters relating to sexuality. While reproductive rights are the right to achieve optimal sexual and reproductive health standards. Including the right to make decisions regarding reproduction without discrimination and violence. Complete information and also the instillation of religious values and norms can be provisions to prevent sexual crimes against children and adolescents (reproductive health, 2020). The purpose of this community service program (PKM) is to improve human resources in terms of being a means of developing knowledge of fertile couples for excellent efforts to prevent menstrual cycle disorders in Bangun Rejo Village, Tanjung Morawa District in 2024 and the establishment of a reproductive health clinic for fertile women. The methods used include 3 stages: 1. Preparation stage At this stage, an official letter process is carried out for activity permits. 2. Implementation stage The second stage is implementation. In each session, before the education, a pretest questionnaire was given, after all participants filled out the questionnaire, the educational material presentation session began, after the counseling, a posttest was given by giving a questionnaire. Stage 3 is the evaluation of the counseling activities through a knowledge questionnaire. For this knowledge variable, a pretest and posttest assessment were carried out. Results Based on the results of the implementation of community service for WUS in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency, Sumatra Province, the average knowledge score before being given education (pretest) was 59.02 while after being given education (posttest) it increased to 79.99. Based on the results of statistical tests with a P value: 0.001